Pembelajaran Daring Menghadapi Fenomena Pandemi Covid-19 (Systematic Literature Review) - Nureyzwan Sabani (Journal of Psychology and Treatment, 2021)
Online learning is considered to be the best solution for learning activities in the midst of the Covid-19 pandemic. Even though it has been agreed, this learning has created a lot of controversy for teachers and learners. Online learning is only effective for assignments, while understanding online learning material is considered difficult for learners. Not all learners have facilities that support online learning activities. The purpose of this review article is to review various articles on online learning to deal with the Covid-19 pandemic phenomenon. The method used is the literature study method with reference sources obtained from scientific works indexed in https://scholar.google.co.id/. The criteria for articles that are used as references are articles published in the past 5-10 years, have an ISSN, and have an h-index. The results of the review of the selected articles stated that the application of online learning should be handled systematically starting from the preparation of the material syllabus, the selection of learning activities, and the learning strategy. Educators should pay attention to three things so that the distance learning process can independent students in learning, namely the task load, time, and understanding of the characteristics of students with various abilities and limitations.